Jurnal KERJASAMA PEMERINTAH TIMOR-LESTE DENGAN INDONESIA DALAM BIDANG PENDIDIKAN 2011 - 2021 - Neri, Septiana De Jesus Neri Jesus; Widya Nugraha, A.A. Bagus Surya; Resen, Putu Titah Kawitri (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2024)
The cooperation between the two countries in the field of education is clear evidence that this collaboration provides excellent opportunities for the people of Timor-Leste to study at a higher level, such as students from Timor-Leste who receive quality undergraduate education and receive input from the Indonesian state or efforts to develop science for the country The purpose of writing this thesis is to describe the process of cooperation between the governments of Timor-Leste and Indonesia in the field of education in the 2011-2021 period. The data collection technique used in this study is similar to bibliographic research, namely collecting data from the literature related to the topic to be discussed and then analyzed. And documents on Timor-Leste's economic capacity to improve the quality of family education, as well as developments and barriers for Timorese students studying in Indonesia, including government and private grants. Cooperation document between Indonesia and Timor-Leste in the field of quality and quality education. Data from magazines, newspapers and internet sites, as well as research reports related to cooperation in the field of education . The results of the analysis show that the collaboration has had a major influence on the country of Timor Leste regarding the quality of education in Timor Leste. Collaboration does not only create peace but also makes the community more prosperous. Rights that have not been fulfilled can be fulfilled, so that people have the same right to education. .